Development of Sustainable Cold Spray Coatings and 3D Additive Manufacturing Components for Repair/Manufacturing Applications: A Critical Review - Pathak, Sunil; Saha, Gobinda C. (MDPI AG, Basel, Switzerland, 2017)
This review article presents the findings of a comprehensive state-of-the-art literature review of the scientific and technological progress of the cold spray process in the field of repair/remanufacturing using the concept of additive manufacturing. A thorough study was conducted on the potential of this technology to form (a) both thin and thick coatings; (b) the ability to fabricate 3D freeform components in a single process, while benefiting from reduced residual stress level compared to conventional thermal spray coatings processes such as high velocity oxy-fuel (HVOF) or plasma spraying. A systematic overview of the process technology, particularly focusing on the suitability of ceramic-metallic (cermet) composite particles used as feedstock in the deposition was conducted; further elaboration was made pertinent to particle impact and bonding mechanisms during the deposition